Konstruksi Sosial Penggunaan Make-up Mahasiswi di Universitas Terbuka - Syerly Martiza; Grace Apriani Sihombing (Konsensus : Jurnal Ilmu Pertahanan, Hukum dan Ilmu Komunikasi, 2024)
This study aims to understand the social constructs that affect the use of makeup in Open University students. The factors discussed include the influence of social media, social factors, culture, and their impact on confidence in meeting existing beauty standards. Using a qualitative descriptive approach, this study explores social norms that contribute to the perception of beauty and the practice of using makeup. The results of the study are expected to provide a deeper understanding of the perception of beauty among female students.